The ratio of denitrification end-products were influenced by soil pH and clay content across different texture classes in Oklahoma soils - Khalifah, Shaima; Foltz, Mary E. (Frontiers in Soil Science, 2024)
Nitrous oxide (N2O) is a potent greenhouse gas that contributes to stratospheric ozone depletion and global climate change. Soil denitrification has two potential end-products, N2O and dinitrogen (N2), and the ratio of these end-products (N2O:(N2O+N2) or the N2O ratio) is controlled by various factors. This study aims to quantify the influence of soil pH on the ratio of denitrification end-products in Oklahoma soils with different soil textures. Six natural grassland soils encompassing three distinct soil textures were incubated in the laboratory under natural and modified pH with an overall tested pH ranging from 2 to 10. Denitrification end-products were measured in the laboratory using the acetylene inhibition technique and further estimated using a process-based biogeochemical model. Both the laboratory and model results showed that soil pH and texture influenced the ratio of the denitrification end-products. Generally, as soil pH increased the N2O ratio decreased, although both lab and model results indicated that this relationship was not linear. Soil texture may have an indirect effect on the N2O ratio, as two soils of the same texture could have different N2O ratios. However, clay percentage of the soil did show a linear positive correlation with the N2O ratio, suggesting components of soil texture may be more influential than others. Overall, soil pH was a controlling factor in the ratio of denitrification end-products and the newly observed nonlinear relationship warrants further study, particularly when considering its effects in different soil textures.